NGC2236: a moderately metal-poor open cluster of Hyades-like age located beyond the Perseus spiral arm - Claria Olmedo, Juan Jose (2007)
New CCD photometry in the Washington system C and T1 passbands down to T1 ∼ 18.5 mag in the field of the northern open cluster NGC 2236 is presented. T1 magnitudes and C − T1 colours for a total of 1162 stars within an area of 13.6 × 13.6 arcmin2 were measured. These CCD data were supplemented with photoelectric CMT1T2 photometry of 13 red giant candidates. The comparison of the cluster (T1, C − T1) colour–magnitude diagram with theoretical isochrones computed for the Washington system yields E(C − T1) = 1.10 ± 0.10 and T1 − MT1 = 13.45 ± 0.25 for log t = 8.80 (t = 600+100 −40 Myr) and Z = 0.008. The derived E(C − T1) value implies E(B − V) = 0.55 ± 0.05. NGC 2236 is then located at 2.5 ± 0.5 kpc from the Sun beyond the Perseus spiral arm and at ∼10.8 kpc from the Galactic centre. A cluster angular diameter of 9.4 arcmin, equivalent to 6.8 pc, was estimated from star counts both within and outside the cluster field. We also derived from the stellar density profile a cluster core radius of rc = 1.7 arcmin (1.2 pc) and an annular corona of rc = 1.8rc (2.2 pc). Five independent Washington abundance indices yield a mean cluster metallicity of [Fe/H] = −0.3 ± 0.2, which is not only in reasonably good agreement with the one obtained from the isochrone fit, but also compatible with the existence of a radial abundance gradient in the Galactic disc. We examined the properties of a sample of 20 known open clusters aligned along the lineof-sight to NGC 2236. Berkeley 27 appears as the farthest and oldest cluster of the studied sample.